GSA HEARING QUESTIONS (Tufts Archival Research Center, 2007)
Marginalia; Questions to be posed at the General Services Administration (GSA) hearing regarding smoking regulations. Refers to 1986 GSA smoking rules and asks what has changed since then. Questions practicality of a smoking ban. Asks what has been done to deal with indoor air quality problems.